ROLE OF SUPPLY CHAIN KNOWLEDGE TRANSFER ON THE PERFORMANCE OF STATE CORPORATIONS IN KENYA - Kariuki, Maina Samuel; Iravo, Prof. Mike Amuhaya; Shale, Dr. Noor Ismail (International Journal of Supply Chain and Logistics, 2018)
Purpose: The purpose of this paper is to determine the role of supply chain knowledge transfer on the performance of state corporations in Kenya. Methodology: A cross-sectional survey and descriptive research design was used in this study. Cross- sectional survey is a method that involves the analysis of data collected from a population, or a representative subset, at one specific point in time. Results: The results showed that supply chain knowledge transfer plays a significant role on the performance of state corporations by both reducing defects in products and services as produced and delivered and also making the business processes more efficient. Conclusion: The study concluded that supply knowledge transfer has a positive and significant relationship with performance of state corporations. Unique contribution to theory, practice and policy: The study recommended that all state corporations should identify their unique knowledge stocks and protect them as intellectual property to become both competitive and sustainable.